Development and evaluation of civil engineering manpower constructability enhancement strategies and tactics - Vorster, S. W.(Schalk Willem),1937- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1992.